Master Mateo in the Cathedral of Santiago de Compostela’s Museum - Yzquierdo Peiró, Ramón (Eikón / Imago, 2018)
In November 2016, the Maestro Mateo exhibition was inaugurated in the Museo Nacional del Prado, the first monograph dedicated to a Galician artist and the medieval art held in this museum in almost two hundred years of history. After the closing of the exhibition in April 2017, it was moved to the Museo Catedral de Santiago, with the addition of new pieces from the funds of both museums, remaining open to the public until February 23th 2018, the date of the 850th anniversary of the life pension that the King Ferdinand II granted Mateo with for the direction of the works in the Cathedral of Compostela, a moment that is usually considered as the starting point of Mateo’s project. Between the years 1168 and 1211, Master Mateo and his workshop team carried out an ambitious project that involved the conclusion of the construction works of the Romanesque cathedral, as well as the adaptation of physical spaces to hold ceremonies that could meet its singularity. Thus, a Galician art with its own personality that would have great later influence was born. Without a doubt, Master Mateo is the great artist of the Cathedral of Santiago and so he is considered, since the aforementioned exhibition, in his Museum, where many important funds are present, through which it is possible to recover the memory of a key project for the cathedral and for the history of medieval art. Since April 2018, the Museo Catedral has a new monographic space dedicated to Master Mateo, with a selection of original pieces that are focused, fundamentally, on the beginning of the project, on the architecture and sculpture of the outer façade of the Portico of Glory, on the stony choir and, finally, on the workshops influenced by Mateo that became his successors throughout the thirteenth century.